569. Pre-retained: Early Intervention for HIV Patients at High Risk of Becoming Un-retained. (26th November 2018) - Abrams-Downey, Alexandra; Joseph, Christopher; Lindner, Rebecca; Rodriguez, Gabriela; Huprikar, Shirish; Sigel, Keith; Chasan, Rachel
Abstract: Background: Poor engagement in HIV care is an established barrier to achieving optimal treatment. Improved engagement is a cornerstone of the national HIV/AIDS strategy and a marker of quality care. However, there is no consensus on strategies for proactive engagement. The objective of this prospective quality improvement pilot project is to demonstrate the effectiveness of early intervention for patients at high risk of becoming un-retained to increase clinic re-engagement and decrease time to re-engagement. Methods: The Jack Martin Fund Clinic (JMFC) is a New York State Designated AIDS Center within the Institute for Advance Medicine at Mount Sinai in Manhattan. Patients at high risk of becoming un-retained were defined as no PCP follow-up in six months. The investigator arranged an appointment and notified patients to confirm. Re-engagement was defined as PCP follow-up within 90 days of intervention. A chart review was completed to collect demographics, co-morbidities and HIV data for the intervention group ( n = 84) and a retrospectively identified control group ( n = 126). Results: The intervention group achieved a statistically significant outcome of increased re-engagement in care and decreased time to re-engagement. Within the intervention group, 67 of 84 patients (80%) followed-up within 90 days compared with only 65 of 126 patients (52%) in the control ( P < 0.01). The time to re-engagement after last PCP visit was also significantly decreased in the intervention group. There were no statistically significant differences between the control and intervention groups regarding race/ethnicity, case management involvement, viral load or co-morbidities. Conclusion: This study demonstrates a low-intensity, high-yield, sustainable intervention that significantly increased re-engagement for HIV patients that are at high risk of becoming un-retained. A unique aspect of this project is the focus on patients who are currently retained, but at risk of falling out of care, as opposed to patients already un-retained. Patients that did not re-engage despite intervention may be at risk for poor retention and earlier care coordination involvement may be considered. Future directions include continuing to follow patients to demonstrate long-term effects of early intervention and re-engagement on rates of retention. Disclosures: All authors: No reported disclosures.